Reaction of the Aswaja Group to the Wahhabism Movement in Aceh - Muammar Muammar (Institut Agama Islam Al-Aziziyah Samalanga, 2023)
The discussion on Wahhabism is not a new discussion for the people of Aceh, since the PUSA era this discussion has been developed, because the PUSA was